2009
DOI: 10.1002/art.24463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug retention rates and causes of drug discontinuation between anti–tumor necrosis factor agents in rheumatoid arthritis

Abstract: Objective. Tumor necrosis factor (TNF) inhibitors have revolutionized the treatment of severe rheumatoid arthritis (RA), yet drug discontinuation is common. The aim of this study was to compare treatment retention rates and specific causes of anti-TNF discontinuation in a population-based RA cohort. Conclusion. In this population, infliximab was associated with higher overall discontinuation rates compared with etanercept and adalimumab, which is mainly due to an increased risk of infusion or allergic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(94 citation statements)
references
References 44 publications
9
72
5
1
Order By: Relevance
“…Similar persistence with the infliximab, adalimumab and etanercept has previously been demonstrated in some studies [45][48], while differences in persistence was observed in others [18], [19], [49][55]. Controversial results of previous studies may be due to different population or methodology (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…Similar persistence with the infliximab, adalimumab and etanercept has previously been demonstrated in some studies [45][48], while differences in persistence was observed in others [18], [19], [49][55]. Controversial results of previous studies may be due to different population or methodology (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…The majority (75 %) of patients were classified as having moderate- or high-disease activity per DAS28 scores. The substantially shorter mean treatment duration of bDMARD therapy (4.7–34.5 weeks) in our study population versus that shown in other studies [23, 24] may be responsible for the suboptimal remission rates that we observed. The mean duration of treatment with etanercept, adalimumab, and infliximab in Italian patients with RA from the Italian Group for the Study of Early Arthritis registry was 3.1, 2.6, and 2.7 years, respectively [23].…”
Section: Discussioncontrasting
confidence: 79%
“…Intermittent therapy or re-exposure after a long treatment-free interval may be associated with an enhanced immune response (or loss of tolerance) to the biological agent, and thus retreated patients must be considered at risk of reactions [5,20,[44][45][46]. Even if some conflicting results have recently been reported [47,48], in our case series, we confirmed a higher incidence of infliximabrelated reactions at the beginning of the second course of therapy [6].…”
Section: Recognition Of Patients At Risksupporting
confidence: 89%